Neurolytic Erector Spinae Plane Block in Advanced Abdominal Carcinoma: A Case Report on Pain Management - MJ Hithish; Samarjit Dey; Koldinne Jagadeeswara Reddy; Nageswara Rao Tangirala (Indian Journal of Pain)
Pain management in patients with advanced abdominal carcinoma remains a significant challenge, particularly in settings where opioid availability is limited. This case report describes the use of a neurolytic erector spinae plane block (ESPB) in a 60-year-old female patient with recurrent periampullary carcinoma, who presented with severe, intractable abdominal pain that was inadequately controlled with a regimen of opioids and adjuvant analgesics. Despite receiving morphine, paracetamol, and pregabalin, the patient continued to experience significant pain and suffered from opioid-induced constipation. Given the complexity of her condition, a neurolytic ESPB was performed at the T12 level under ultrasound guidance. The procedure provided rapid and sustained pain relief, reducing her Numerical Rating Scale pain score from 8/10 to 1/10 within an hour postprocedure. Over the following months, the patient’s pain remained well controlled with minimal medication, allowing her to resume daily activities. This case highlights the potential of neurolytic ESPB as a valuable addition to the multimodal pain management strategies for cancer patients, offering effective pain relief with a favorable safety profile.